Household Energy Supply and Use in Yemen : Volume 2. Annexes - World Bank (World Bank, Washington, DC, 2014)
Yemen's Second Five Year Plan for Social and Economic Development (2001-2005) and Poverty Reduction Strategy Paper (PRSP, 2003-05) provide a framework to reduce poverty through national actions and development assistance. The PRSP recommends a gradual lifting of subsidies for petroleum products, phased to ensure that energy price reform does not aggravate poverty in a country with an already high percentage of poor people. The PRSP also promotes policies that will lead to better access to energy. This report deals with the relationship between energy policy and household welfare. By establishing the facts about household energy supply and use, the impact of new energy policies on the poor can be anticipated with greater confidence. A household energy strategy forms an essential element of overall energy sector planning. At the request of the Ministry of Planning and International Cooperation (MOPIC), the joint World Bank/United Nations Development Program Energy Sector Management Assistance Program (ESMAP) carried out a study to examine the energy policies which would, if implemented, contribute to poverty reduction in Yemen. The study reviewed the main beneficiaries of energy subsidies and the likely impact of their removal. This report, Volume I, summarizes the results of the study and outlines a number of policy options intended to achieve the energy sector goals of economic efficiency, financial cost recovery, environmental sustainability and social equity. A separate report, Volume II, contains a set of ten annexes.